2018
DOI: 10.1186/s40360-018-0269-3
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-sulfamethoxazole induced circulatory shock in a human immunodeficiency virus uninfected patient: a case report and review

Abstract: BackgroundSevere systemic reactions resembling septic shock have been described following trimethoprim-sulfamethoxazole (TMP-SMX) administration. Nearly all cases described in the literature occurred in HIV-infected patients.Case presentationWe present a 42-year-old woman with a history of systemic lupus erythematosus (SLE) who was admitted to the Intensive Care Unit (ICU) twice with fever and circulatory shock after taking a dose of TMP-SMX 800–160 mg. She had no respiratory distress, urticarial rash or eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Histopathologic findings for this entity have yet to be well described but have been found to lack the main histologic features of AGEP. 25 In our case, the cutaneous findings and histopathologic evaluation were both consistent with AGEP, as was the EuroSCAR AGEP validation score.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Histopathologic findings for this entity have yet to be well described but have been found to lack the main histologic features of AGEP. 25 In our case, the cutaneous findings and histopathologic evaluation were both consistent with AGEP, as was the EuroSCAR AGEP validation score.…”
Section: Discussionsupporting
confidence: 82%
“…3 There have also been reports of circulatory shock after administration of trimethoprimsulfamethoxazole, most commonly associated with human immunodeficiency virus. 25 Although these patients may have hypotension, hypoxemia, and renal and liver involvement, the classical cutaneous findings include conjunctivitis, maculopapular rash, and "sunburn-like" generalized erythema without pustules. 25 In patients who present with generalized erythema and associated hypotension after taking trimethoprim-sulfamethoxazole, a biopsy should be considered to distinguish early AGEP from trimethoprim-sulfamethoxazole-induced circulatory shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
ypersensitivity reactions (HSRs) with hemodynamic changes have been described after administration of trimethoprim-sulfamethoxazole (TMP-SMX). 1 Various names exist for this reaction, including TMP-SMX induced circulatory shock, and atypical, unusual, anaphylactic-like, or severe shock-like reaction to TMP-SMX. 1,2 This systemic reaction was initially described in patients with HIV.
…”
mentioning
confidence: 99%
“…Multiple heterogeneous factors are responsible for the substantial risk in HIV-infected patients, including polypharmacy, slow acetylator phenotype, glutathione deficiency, a CD4 + T Cell count of <200 cells/mm 3 or >25 cells/mm 3 , latent cytomegalovirus and Epstein-Barr virus infections ( Carr and Cooper, 2000 ). It was reported that the incidence of serious adverse drug reactions (sADRs) of trimethoprim-sulfamethoxazole in HIV-infected persons correlated with the HIV load ( Coopman, 1993 ; Liu et al, 2018 ). Moreover, Rabaud et al studied 592 HIV-infected patients who were first treated with cotrimoxazole during the Delta trial (a randomized, double-blind, controlled trial).…”
Section: Discussionmentioning
confidence: 99%